Proceedings of research in clinical practice 2011. - Spiliotis, I; Kelley, T; Barker, C; Achaibar, K; Robertson, K; Cindrova-Davies, T; Burton, G; Charnock-Jones, S; Ibitoye, RT; Ibitoye, RT; Twomey, P; Achaibar, K; et al. (2012)
The skeletal muscle proteins, dysferlin (DYSF) and myoferlin (MYOF) have been demonstrated by mass spectrometry to be present in the apical syncytiotrophoblast of the human placenta, where they may play a role in membrane repair. Immunohistochemistry and immunoblotting were performed on placental samples to localize and quantify DYSF and MYOF in first trimester, term and pathological pregnancies. Here, we show that placental DYSF and MYOF are reduced in labour but only MYOF is elevated in cases of intrauterine growth restriction (IUGR) and pre-eclampsia, relative to Caesarean section controls. In term villous explants cultured for 24 h, DYSF levels decreased, compared to T(0) controls, while MYOF levels remained static. Additionally, trophoblastic BeWo cells show reduced levels of DYSF but unchanged levels of MYOF under conditions of oxidative stress, while DYSF levels in microparticles isolated from the supernatant increase. These findings suggest that DYSF but not MYOF plays a pivotal role in membrane repair mechanisms in the human placenta and that dysferlin microparticles could potentially represent a novel biomarker for pre-eclampsia. Ethical approval: Samples were collected with informed written consent of the patients and Local Research Committee approval. Conflict of interest: none declared.